The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1101/2020.09.16.20195552
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How the clinical research community responded to the COVID-19 pandemic: An analysis of the COVID-19 clinical studies in ClinicalTrials.gov

Abstract: Objective: The novel coronavirus disease (COVID-19), broke out in December 2019, is a global pandemic. Rapidly in the past few months, a large number of clinical studies have been initiated worldwide to find effective therapeutics, vaccines, and preventive strategies. In this study, we aim to understand the landscape of COVID-19 clinical research and identify the gaps and issues that may cause difficulty in recruitment and the lack of population representativeness. Materials and Methods: We analyzed 2,034 CO… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…COVID‐19 has inspired a wide array of systematic reviews 21 , 22 , 23 , 24 ; however, our large‐scale systematic review is the first to provide a synthesis of all existing COVID‐19 related RCTs with published findings and their reporting of key demographic and clinical characteristics by time period and study types through June 2021. While simple demographic statistics (e.g., age) and comorbidities (e.g., hypertension) were frequently reported on, more complex and sensitive demographics (e.g., race) and comorbidities (e.g., respiratory illness) were much less common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID‐19 has inspired a wide array of systematic reviews 21 , 22 , 23 , 24 ; however, our large‐scale systematic review is the first to provide a synthesis of all existing COVID‐19 related RCTs with published findings and their reporting of key demographic and clinical characteristics by time period and study types through June 2021. While simple demographic statistics (e.g., age) and comorbidities (e.g., hypertension) were frequently reported on, more complex and sensitive demographics (e.g., race) and comorbidities (e.g., respiratory illness) were much less common.…”
Section: Discussionmentioning
confidence: 99%
“…This problem is likely compounded in severely ill patients, who may be completely unresponsive. Further, the results of He et al suggest that some chronic conditions such as cancer, heart failure, hypertension, chronic kidney disease, and COPD were eligibility criteria in 2.76%–8.42% of studies; such exclusion and inclusion criteria would not likely appear in the tables within published manuscripts 21 . Unfortunately, these low rates of reporting make it difficult to understand the generalizability of these trials to specific target populations.…”
Section: Discussionmentioning
confidence: 99%
“…perpetuity. preprint (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in The copyright holder for this this version posted January 4, 2021. ; https://doi.org/10.1101/2020.12.29.20248975 doi: medRxiv preprint He Z. et al [38] analysed 2,034 COVID-19 studies registered in ClinicalTrials.gov as of 18 th June 2020 and reported that the five most frequently tested drugs were HCQ (n = 148), AZM (n = 46), tocilizumab (n = 29), lopinavir (n = 20), and ritonavir (n =20). We did not embark on such a deep review, but from the 3,904 registered trials, as of 5 th November 2020, a quick scan showed that HCQ and AZM are still highly preferred, with 262 records mentioning the use of HCQ alone or in combination with AZM.…”
Section: Discussionmentioning
confidence: 99%
“…He Z. et al [38] analysed 2,034 COVID-19 studies registered in ClinicalTrials.gov as of 18th June 2020 and reported that the five most frequently tested drugs were HCQ (n = 148), AZM (n = 46), tocilizumab (n = 29), lopinavir (n = 20), and ritonavir (n =20). We did not embark on such a deep review, but from the 3,904 registered trials, as of 5 th November 2020, a quick scan showed that HCQ and AZM are still highly preferred, with 262 records mentioning the use of HCQ alone or in combination with AZM.…”
Section: Discussionmentioning
confidence: 99%
“…He Z. et al [56] analyzed 2,034 COVID-19 studies registered on ClinicalTrials.gov as of 18 June 2020 and reported that the five most frequently tested drugs were HCQ (n = 148), AZM (n = 46), tocilizumab (n = 29), lopinavir (n = 20), and ritonavir (n = 20). We did not conduct a deep review, but of the 3,904 registered trials, as of 5 November 2020, a quick scan showed that HCQ and AZM were still highly preferred, with 262 records mentioning the use of HCQ alone or in combination with AZM.…”
Section: Discussionmentioning
confidence: 99%